Restaurant revenue management : study of cafe cartel. - Huang, Stuart Weirong. (2008)
Restaurants have fixed capacity and seats are assets of a restaurant. Due to the limited nature of seating, restaurant managers often face the trouble of which party of customers to entertain when there is a queue. For them, having the right information of which party size is profitable is beneficial as it allows them to entertain the right customer group effectively. This paper seeks to find out the profitable target party size through a 2 week observation study at 2 different branches of restaurants. Managerial implications of other factors that might influence spending are also discussed and tested.